‘Abdurrahman ad-Dakhil (Superman in Islamic History: 756 CE-788 CE) - Nofrianti, Mami; Pertiwi, Dian (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2022)
This article aims at discussing the struggle of one of the Umayyads’ descendants who was able to escape from the Abbasid army from the city of Damascus (Syria) to Andalusia (Al-Andalus). He managed to re-establish the power of the Umayyads in Andalusia after the collapse of their power in Damascus, due to the Abbasid army attack. A qualitative method with library research-based was used in conducting this study, the data were analyzed by using qualitative descriptive approach, technical descriptive analysis, and content analysis. The results showed that ‘Abdurrahman Ad-Dakhil had great talent and strong influence with the result that Islamic Spain could be united under his rule. He was very instrumental in building a government in Andalusia in such a way that the Andalusian State could compete with the influence of the Abbasid Daulahh’s power in Baghdad. Thus, he is one of the most important figures in Islamic history. He became an inspirational figure because of having persistency, intelligence, thorough struggle, and upholding Islamic law.